Incarcerated Women as Facilitators: A Preliminary Review of Motivations and Skill Development in Group Leadership Settings - Chaundra L. Whitehead (Adult Education Research Conference, 2015)
The United States has the highest incarceration rate in the world with about 500 prisoners per 100,000 residents (Tsai & Scommegna, 2012). There are currently about 7 million offenders under the supervision of the adult correctional systems in the U.S. There are numerous statistics demonstrating the growth and scope of women in prison. The rate of increase has been about twice that of their male counterparts. The number of incarcerated woman has jumped a shocking 757 percent since 1977 (Talvi, 2007, p.3). As a result of these growing inmate populations there has been an increased focus on the topic of rehabilitative programming and impacting recidivism rates. Violence, violence prevention and conflict resolution skills in correctional facilities should be of concern considering prisons are simply microcosms concentrated with the troubles of society. Alternatives to Violence Project (AVP) has been working to reduce violence in prisons since 1975 and has now spread to over 50 countries in prisons, schools, communities and business settings (avpusa.org). One aspect which makes AVP distinctive from other conflict resolution and anger programs is that is facilitated by non-professionals, trained inmates and community volunteers. Conflict resolution training, while limited, serves as a topic of great value in the process of developing skills that incarcerated individuals can use upon release. The purpose of this round table is to discuss the reported motivations and skill development of 22 incarcerated women who serve as inside facilitators for AVP in a South Florida prison. This preliminary data will contribute to a phenomenological study which will examine the lived experiences of incarcerated facilitators of AVP and explore their experiences, feelings and beliefs of their roles, as well as views on their impact on those they train.